INNOVATIVE SOLUTIONS AND SUSTAINABLE PRODUCTION: ENERGY-EFFICIENT TECHNOLOGIES AND REDUCING “SUGAR DEPENDENCE” IN THE MANUFACTURE OF HEALTHY LOW-GI FLAKES - Kovalenko, Ihor (SWorld-Ger Conference proceedings, 2025)
The article examines the development of an innovative combined heating system for a tunnel dehydrator and drying chamber that utilizes biogas, solar energy, and heat recovery. The proposed technological solutions aim to enhance production energy efficienc